2013
DOI: 10.1155/2013/260395
|View full text |Cite
|
Sign up to set email alerts
|

A Phylogenetic Analysis of Greek Isolates ofAspergillusSpecies Based on Morphology and Nuclear and Mitochondrial Gene Sequences

Abstract: Aspergillus species originating from Greece were examined by morphological and molecular criteria to explore the diversity of this genus. The phylogenetic relationships of these species were determined using sequences from the ITS and IGS region of the nuclear rRNA gene complex, two nuclear genes (β-tubulin (benA) and RNA polymerase II second largest subunit (rpb2)) and two mitochondrial genes (small rRNA subunit (rns) and cytochrome oxidase subunit I (cox1)) and, where available, related sequences from databa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 56 publications
3
23
0
Order By: Relevance
“…Interestingly, we did not find clear separation between toxigenic and non-toxigenic A. flavus isolates when analyzing the ITS sequences as they were interspersed. Similar findings were reported by Baird et al [38] who stated that ITS markers failed to discriminate the toxigenic from the non-toxigenic isolates of A. flavus. Although phylogenetic relationships among A. flavus strains, isolated from different substrates and geographical regions, using the ITS domain has been reported by many researchers [39], better inferences of intra-species diversity will require exploration of multiple/different genomic loci.…”
Section: Discussionsupporting
confidence: 90%
“…Interestingly, we did not find clear separation between toxigenic and non-toxigenic A. flavus isolates when analyzing the ITS sequences as they were interspersed. Similar findings were reported by Baird et al [38] who stated that ITS markers failed to discriminate the toxigenic from the non-toxigenic isolates of A. flavus. Although phylogenetic relationships among A. flavus strains, isolated from different substrates and geographical regions, using the ITS domain has been reported by many researchers [39], better inferences of intra-species diversity will require exploration of multiple/different genomic loci.…”
Section: Discussionsupporting
confidence: 90%
“…The evolutionary tree showed that isolate-1 closely relates to A. unguis, while isolate-2 and 3 are related to A. niger and A. flavus, respectively. Similar phylogenetic relationships based on ITS and IGS regions of the nuclear rRNA gene complex of fungus have been reported (Krimitzas et al, 2013). Significant efforts have also been reported by Chiba et al (2014) in which they developed phylogenetic tree analysis of aflatoxigenic and other non-aflatoxigenic species of Aspergillus group based on ITS sequences.…”
Section: Discussionsupporting
confidence: 67%
“…The morphology of the ascospores including colour, shape, size and ornamentation are of particular importance for species delineation and identification in Emericella (Thom and Raper, 1939, Christensen and Raper, 1978, Horie, 1980, Christensen and States, 1982, Ismail et al., 1995, Zalar et al., 2008, Matsuzawa et al., 2012, Guarro et al., 2012, Kritmitzas et al. 2013).…”
Section: Introductionmentioning
confidence: 99%